Creation of glass-characteristic point defects in crystalline SiO2 by 2.5 MeV electrons and by fast neutrons - Skuja, Linards; Ollier, Nadège; Kajihara, Koichi; Smits, Krisjanis (Elsevier B.V., 2019)
Point defects in crystalline SiO2, created by 2.5 MeV electron irradiation at dose below the amorphization threshold or by fast neutrons, were compared by luminescence spectroscopy. Oxygen dangling bonds (“non-bridging oxygen hole centers”, NBOHCs), peculiar to amorphous state of SiO2, were detected for the first time in electron-irradiated non-amorphized α-quartz crystal. Their presence may signal the formation of nucleation centers in crystal structure as the first step to radiation-induced amorphization. Compared to crystal, irradiated by 1019 cm−2 fast neutrons, their concentration was over 100 times lower, and their inhomogeneous broadening was at least 2.5 times smaller. Divalent silicons (“silicon oxygen deficiency centers”, SiODC(II)), inherent to oxygen-deficient or irradiated SiO2 glass, were detected in neutron-irradiated (1019 n/cm2) α-quartz but were not found after the electron irradiation. Radiation-induced interstitial O2 molecules, characteristic to irradiated glassy SiO2 and other oxide glasses, are found in α-quartz only after neutron irradiation. The oxygen atoms, displaced by the 2.5 MeV e− irradiation of α-quartz for fluences up to 1019 e−/cm2 evidently stays entirely in the peroxy linkage (Si-O-O-Si bond) form.
The support from M -ERANET project “MyND” is acknowledged. K.K. was partially supported by the Collaborative Research Project of Laboratory for Materials and Structures, Tokyo Institute of Technology . Visiting researcher support from Ecole Polytechnique, Palaiseau is appreciated. Mr. Olivier Cavani is thanked for the expert help with irradiations.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Amorphization; Dangling bonds; Electron irradiation; Luminescence; Quartz; Silica glass